(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2023)
This article explains the concept and content of strategic management. Methods of effective strategic management at enterprises and organizations, ways to ensure the competitiveness of industrial enterprises and improve the efficiency of planning are being studied.